2020
DOI: 10.18632/oncotarget.27534
|View full text |Cite
|
Sign up to set email alerts
|

Association of germline genetic variants with TMPRSS2-ERG fusion status in prostate cancer

Abstract: Introduction: Oncogenic activation of ERG resulting from TMPRSS2-ERG gene fusion is a key molecular genetic alteration in prostate cancer (CaP). The frequency of ERG fusion is variable by race; however, there are limited data available on germline polymorphisms associating with ERG fusion status. The goal of this study is to identify the inherited risk variants associating with ERG status of CaP. Materials and Methods: SNP genotyping was performed on the Illumina platform using Infinium Oncoarray SNP chip on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…In fact, these 'common' ETV1 fusions were not observed at all in TCGA tumour samples. It thus appears that the frequency of fusion events in PcTas9 is considerably higher than the frequency normally observed in Caucasian tumour cohorts (~40%–50%) 3–6 and suggests an underlying inherited predisposition to the formation of these events in this family. In fact, there is now a strong body of evidence supporting this theory, 3,12–15 including two recent and very diverse studies 29,30 .…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…In fact, these 'common' ETV1 fusions were not observed at all in TCGA tumour samples. It thus appears that the frequency of fusion events in PcTas9 is considerably higher than the frequency normally observed in Caucasian tumour cohorts (~40%–50%) 3–6 and suggests an underlying inherited predisposition to the formation of these events in this family. In fact, there is now a strong body of evidence supporting this theory, 3,12–15 including two recent and very diverse studies 29,30 .…”
Section: Discussionmentioning
confidence: 62%
“…It thus appears that the frequency of fusion events in PcTas9 is considerably higher than the frequency normally observed in Caucasian tumour cohorts (~40%–50%) 3–6 and suggests an underlying inherited predisposition to the formation of these events in this family. In fact, there is now a strong body of evidence supporting this theory, 3,12–15 including two recent and very diverse studies 29,30 . A transcriptome‐wide association study by Emami et al 29 observed a positive correlation between imputed TMPRSS2 expression levels in normal prostate tissue (as predicted by germline cis ‐expression quantitative trait loci) and ERG expression in TMPRSS2:ERG fusion‐positive tumour samples 29 .…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations